The future role of the psychiatrist in Europe – a UEMS perspective - Hermans, M. (Die Psychiatrie, 2014)
The author presents his personal opinion inviting to discussion on the possible future role of psychiatrists. His view is based upon the many contacts with psychiatrists all over Europe, academicians and everyday professionals, as well as the familiarity with the literature. The list of papers referred to is based upon (1) the general interest concerning the subject when representing ideas also worded elsewhere, (2) the accessibility to psychiatrists and mental health professionals in Germany, (3) being costless downloadable for non-subscribers and (4) for some geographic aspects (e.g. Belgium, Spain, Sweden) and the latest scientific issues, addressing some authors directly.
Keywords: Psychiatry’s future; psychiatry as profession; professional recruitment; UEMS psychiatry